Hubungan Peran Ibu dengan Konsep Diri Anak Usia 3-5 Tahun - Eny Pemilu Kusparlina (2-TRIK: TUNAS-TUNAS RISET KESEHATAN, 2020)
Self concept is overall perception a person has about himself. The self concept refers to the connection of attitudes and beliefs we hold about ourselves. Achievement of roles mother is a child who has a self concept relatively stable gained through socialization a lifetime that determines how mother explains and feels the events as well his perception of the child's response. The purpose of this study was to knowed the relationship of mother role with self-concept of children aged 3-5 years. The type of this research was descriptive correlation with cross sectional approach. The research was done in KB/TK Al Hidayah I Manisrejo. The population of this study was all mothers who have children 3-5 year in KB/TK Al Hidayah I Manisrejo District Taman Madiun City with the number of 30 children so that the whole was used as research sample with population research technique. The data collection tool was questionnaires and documentation. Data were analyzed using Kendall Tau test. The results showed that the role of mothers positively related to the self-concept of children in KB/TK Al Hidayah I Manisrejo this is evident from the correlation value of 0.644 with a significance of 0.000